The Effect of Asset Tangibility and Investment Decisions on Firm Value with Profitability as Moderating Variable - Barida Syava Noor Zahra; Murtanto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to examine the effect of asset tangibility and investment decisions on firm value, while also evaluating the moderating role of profitability. The study utilizes secondary data in the form of annual reports of the companies. The population of this study consists of companies in the industrial sector listed in Indonesia Stock Exchange (IDX) for the 2022-2024 period. Sample selection was carried out using a purposive sampling technique, with total 124 companies’ data points that satisfied the established selection criteria. The data analysis method used id quantitative utilizing SPSS. The empirical findings reveal that investment decisions have a positive effect on firm value, while asset tangibility is not found to effect firm value, and profitability does not strengthen the effect of asset tangibility and investment decisions on firm value.